1992
DOI: 10.1063/1.108288
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of 1.54-μm-luminescence Er3+ implanted in Si

Abstract: Electrochemical Er doping of porous silicon and its roomtemperature luminescence at 1.54 μm Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
97
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(107 citation statements)
references
References 12 publications
9
97
1
Order By: Relevance
“…Knowledge of the microscopic structures of the rare earth impurities in semiconductor hosts is very important for fabricating efficient injection-type light emitting devices. To understand the microscopic structures, the electron spin resonance ͑ESR͒ measurements, [1][2][3][4][5][6][7] the extended x-ray absorption fine structure ͑EXAFS͒ measurements, 8,9 and the Rutherford backscattering ͑RBS͒ channeling measurements [10][11][12][13] have been performed on Er-doped GaAs, Er-doped Si, and Yb-doped InP.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the microscopic structures of the rare earth impurities in semiconductor hosts is very important for fabricating efficient injection-type light emitting devices. To understand the microscopic structures, the electron spin resonance ͑ESR͒ measurements, [1][2][3][4][5][6][7] the extended x-ray absorption fine structure ͑EXAFS͒ measurements, 8,9 and the Rutherford backscattering ͑RBS͒ channeling measurements [10][11][12][13] have been performed on Er-doped GaAs, Er-doped Si, and Yb-doped InP.…”
Section: Introductionmentioning
confidence: 99%
“…Extended X-ray absorption fine structure (EXAFS) measurements of Er-implanted, high O impurity Czochralski-grown Si, which exhibit strong PL at 1.54 µm, show Er is six-fold coordinated to oxygen [8]. Strong PL can also be observed from Er and O coimplanted Si [9].…”
Section: Introductionmentioning
confidence: 82%
“…Strong PL can also be observed from Er and O coimplanted Si [9]. By contrast, in low O impurity FZ Si, no PL was observed and Er was coordinated with 12 Si atoms [8]. Contradictory Rutherford backscattering (RBS) measurements have indicated that Er implanted in Si is located [10], and is not located [11], at an interstitial site.…”
Section: Introductionmentioning
confidence: 94%
“…ErSi 2 ) and rare earth oxide precipitates in CZ Si (e.g. Er 2 O 3 ), we have now developed a model on the basis of simple diffusion and capture kinetics of Er and O, which allows us to compare possible scenarios to the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Good optical activation of Er may be obtained, e.g., by Er implantation into O-rich Si (CZ Si or O co-doped Si) followed by annealing at high temperatures (900-1000°C). Extended X-ray absorption fine structure (EXAFS) experiments [2,3] have shown that this procedure results in the majority of Er within Er 2 O 3 -like surroundings, while Er implantation into oxygen-lean FZ Si produces an ErSi 2 -like neighbourhood. On the other hand, transmission electron microscopy (TEM) has revealed the formation of precipitates in both Er implanted CZ and FZ Si annealed at 900°C [4].…”
mentioning
confidence: 99%